KONFLIK ANTAR ETNIS Studi : Konflik Antar Etnis Minangkabau dengan Etnis Jawa di Nagari Silaut Kecamatan Silaut Kabupaten Pesisir Selatan - Putra, Novi Eka (Pendidikan Sosiologi, 2014)
Conflict between Minangkabu and Jawa ethnic in Nagari Silaut Kecamatan Silaut Kabupaten Pesisir Selatan. The purpose of this research is to describe the main conflict that happened between Minangkabu and Jawa ethnic in Nagari Silaut Kecamatan Silaut Kabupaten Pesisir Selatan and to describe the forms of conflict that appear between Minangkabau and Jawa ethnic in Nagari Silaut Kecamatan Silaut Kabupaten Pesisir Selatan. The theory that used in this research is conflict theory by Lewis A Coser. The result of this research shows that the main conflict between Minangkabau and Jawa ethnic in Nagari Silaut Kecamatan Silaut Kabupaten Pesisir Selatan are first, economic discrepancy, second struggle of Sambungo beach right management. The form of Minangkabau and Jawa ethnic conflicts are first, hause key taking. Second, disturbance. Third, streetblokade.